Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas, dan Tata Kelola Perusahaan terhadap Sustainability reporting - Hania Sulistin Rahayu; Indah Permata Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of corporate governance, firm size, profitability, and liquidity on sustainability report disclosure among companies listed on the Indonesia Stock Exchange. Sustainability report serves as a crucial tool for communicating a company's social and environmental responsibilities to stakeholders. Using a quantitative approach and multiple linear regression method, secondary data from annual reports for the period 2019–2023 were analyzed. The results indicate that corporate governance and profitability have a significant positive effect on sustainability reportdisclosure. Meanwhile, firm size and liquidity do not show a significant influence. These findings support legitimacy theory, which suggests that firms tend to enhance transparency to gain social support. The practical implications of this study provide insights for management and policymakers in designing more effective sustainability strategies.